AFIKS PEMBENTUK VERBA BAHASA JAWA DIALEK TEGAL KAJIAN DESKRIPTIF STRUKTURAL - Herawati, Deni; Hermintoyo*, Muhammad; Amin*, Mujid Farihul (Sastra Indonesia, Fakultas Ilmu Budaya, 2012)
AbstractRegional variations in language used by a small group of speakers of the languagein which there are elements of language caused by geographical factors. Theconcept was used as a description of the linguistic characteristics of a marker orthe difference between a dialect / subdialek with each other. This study wasassociated with problems related dialects as speakers that use the Java language asa dialect of Tegal different regional languages and dialects other areas thestandard Java language. Tegal Javanese dialect has the hallmark of pronunciation,which is equal to what is spoken is written. This study aims to find the verbformingaffixesareJavanesedialectinTegal,functionsandmeaningsthatemergeaftera process of affixation. The results showed that verbs can be formed througha process of affixation whether it comes from the verb, noun, adjective, adverbial,dannumeralia. Affixes in the verb form of the Java language is a dialect of Tegalaffixes ng-, m-, n-, ny-, di-, his, her,-em-,-i,-an,-na,-ni, di-na , in-i, n-na, ng-i, eachof which has the function and meaning